Vitamina D, qualidade de vida e alto risco de depressão em indivíduos com Diabetes Mellitus Tipo 2 e Doença Renal Diabética: um estudo transversal - REIS, Melissa de Sá Oliveira dos (Universidade Federal do Pará, 2025)
Clinical Depression is highly prevalent in patients living with Diabetic Kidney Disease (DKD) and Diabetes Mellitus 2 (DM2) and is related to high morbidity and mortality, in addition, Health-Related Quality of Life (HRQoL) is also potentially impacted in these patients. Vitamin D (VD) deficiency has been associated with depression and worse HRQoL in patients with DRD. This study aims to investigate the association between vitamin D levels, HRQOL and depression in patients with DRD who are not receiving dialysis treatment. To this end, this was a cross-sectional study, which included 51 patients with DM2 and DRD, not on dialysis and with severely elevated albuminuria, treated at the João de Barros Barreto University Hospital. To measure depressive symptoms (SD), the Beck Depression Inventory (BDI) was used and HRQoL was analyzed using the EQ-5D-5L instrument. Additionally, the Glomerular Filtration Rate estimate was calculated by CKD-EPI Refit. Result: The prevalence of depression was 46.9% and was strongly associated with quality of life levels assessed by the EQ-5D. Impacting both domains and utility indices (Domain “Pain and discomfort” 0.7±0.8 vs 1.1±0.8, p<0.05; Utility index “United States” 0.89 [0.78-1] vs 0.71[0.60-0.84], p<0.05). Worse quality of life was even associated with the severity of depression. With regard to DV, it directly impacted HRQoL, but no direct association was found between DV and depression. Models with simple logistic regression showed that patients with peripheral neuropathy (PN) had a six times greater risk of experiencing depression (OR 6.56, R²=0.12, p<0.05). Additionally, the duration of DM2 was also important, with each year of illness increasing the risk of depression by 12% (OR 1.135, R²=0.18, p<0.05). The data suggested that depression has a high prevalence in patients with T2DM and DRD and is strongly associated with low levels of HRQoL. HV impacted quality of life, but was not directly associated with the prevalence and severity of depression.